2014
DOI: 10.1039/c4cc06029f
|View full text |Cite
|
Sign up to set email alerts
|

Crown ethers attenuate aggregation of amyloid beta of Alzheimer's disease

Abstract: The stagnant state of drug development for Alzheimer’s disease demands new approaches for seeking promising candidates. In this report, we reasoned that non-covalent modification of amyloid beta (Aβ) peptide by crown ethers could inhibit its aggregation. To specifically target Aβs, a conjugate of Pittsburgh compound B (PiB) and 12-crown-4 ether (termed PiB-C) was synthesized. Our results indicated that the conjugate could significantly reduce the aggregation of Aβs in vitro. In addition, by two-photon microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 35 publications
4
34
0
Order By: Relevance
“…Given the amyloid-like properties of small metabolite assemblies and the ability of known amyloid inhibitors to inhibit the formation of phenylalanine [32][33][34]40 and tyrosine 33,41 assemblies, it is of great interest to examine whether chemical agents known to inhibit the assembly of protein and peptide-based amyloid structures can also restrict the formation of these metabolite fibrils. Furthermore, owing to the similarity between the protein and metabolite assemblies, the later can serve as an attractive minimalistic model to probe the mechanism of amyloid inhibition, which is yet to be fully deciphered.…”
mentioning
confidence: 99%
“…Given the amyloid-like properties of small metabolite assemblies and the ability of known amyloid inhibitors to inhibit the formation of phenylalanine [32][33][34]40 and tyrosine 33,41 assemblies, it is of great interest to examine whether chemical agents known to inhibit the assembly of protein and peptide-based amyloid structures can also restrict the formation of these metabolite fibrils. Furthermore, owing to the similarity between the protein and metabolite assemblies, the later can serve as an attractive minimalistic model to probe the mechanism of amyloid inhibition, which is yet to be fully deciphered.…”
mentioning
confidence: 99%
“…Previously we found that 12-crown-4 could attenuate the aggregation of Aβs. 13 Reportedly, crown ethers could form hydrogen bonds with positively charged amino groups (e.g. lysine, arginine, histidine) to shield the charge, 14 and the sequence of Aβ peptides contains important lysine (K16), a crucial amino acid that forms inter-sheet salt bridges and 6 promotes mis-folding of Aβ.…”
Section: Resultsmentioning
confidence: 99%
“…9 Previously, we found that 12-crown-4 showed decreased level of Aβ aggregates, confirmed by fluorescence assay and TEM observation. 13 To further prove that the charge editing effect could break the salt bridge of Aβ and change protein aggregation behaviors, SDS-page gel studies were performed. As expected, the addition of 12-crown-4, 18-crown-6 and Orange G significantly changed aggregation behaviors of Aβs, as indicated by reduced aggregation of low molecular weight of Aβs ( Supplementary Fig.10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the molecules with abilities to inhibit or reduce the level of toxic oligomer and pathological fibril of Aβ may be used as drugs for AD treatment. Previously, positive results from the testing this strategy had been received by treatment with small ether compounds such as cycloalkyl ether, noladin ether, and 12-crown 4 cyclic polyether [16][17][18][19]. Particularly, the latter with a cyclic structure showed in silico and in vitro anti-Aβ aggregation, and it reduced its toxicity in Aβ42treated SH-SY5Y cells [18,19].…”
Section: Introductionmentioning
confidence: 99%